Productivity of White-Tailed Deer in Central Wisconsin - Clark, William H. (University of Wisconsin-Stevens Point, College of Natural Resources, 1981)
Fetal counts and ovarian analyses were used to assess productivity of 90 female white-tailed deer (Odocoileus virginianus) collected in central Wisconsin during the springs of 1978 and 1979. Six of 51 (12%) doe fawns contained a single fetus (1.00 each), differing significantly (P<0.05) from the fetal rate for 13 pregnant yearling does containing 20 fetuses (1.54 each). The average fetal rate for 21 gravid adult does containing 41 fetuses (1.95 each) was significantly different (P<0.05) from that for fawns and yearlings. Ovarian analyses revealed a single corpus luteum in each of 8 doe fawns. Two of these fawns had no fetuses indicating an ovum loss of 25%. The ovulation rate in fawns (1.00) was significantly different (P<0.05) from that of yearlings (1.69) and adults (2.10). Twenty-two corpora lutea were found in ovaries of l3 gravid yearling does, but 9.1% of the ova were not fertilized. The ovulation rate in adults was significantly different ( P< 0.05) from that in yearlings, and ovum loss was only 4.5%. Almost half (49%) of the 61 fetuses collected were males. A chi-square test indicated that the sex ratio of 97 males to 100 females did not differ from 1:1 ( P> 0.05). Over half (56%) of the litters were twins; 15 of 36 litters (42%) were singles. No twin litters were from doe fawns; triplet litters were recovered from 2 adult does. The percentage of males was the same (53%) for single and twin litters. Breeding activity was greatest during a 3-week period from 8 November to 5 December, when 67% of the does examined were bred. Breeding in adult does was greatest during the week of 15 to 21 November and in yearling does the following week (22 to 28 November) . Except for 1 doe fawn bred during the week of 8 to 14 November, breeding among doe fawns occurred about 1 month later than adult does. Reproductive tracts also were collected from deer in 2 range types (forested and agricultural) during the 1978 gun deer season. Thirty-six of 39 (92%) does over l year of age from the forested area had ovulated by 26 November. No significant difference (P>0.05) existed among ovulation rates for fawns (1.33), yearlings (1.36), and adults (1.39). Five of 6 yearling does and all 9 adult does from the agricultural region contained corpora lutea of pregnancy. Differences in ovulation rates for yearlings (2.00) and adults (2 .11) were not significant (P >0.05).